Students’ Interest Level In Learning Listening By Using Note-Taking Strategy - Nurwanti; Chindy Lorena Chansa (CV. Eureka Murakabi Abadi, 2023)
This research aims to find out the students’ interest level of learning listening by using Note-Taking Strategy. This research is descriptive quantitative. The population of this research was 208 students, and the sample of it was 30 students. The finding of research is there were 11 students or 36.67% who chose Very High option, in which 19 students with the percentage of 63.33 were in the High Option. The total score of students is 2534 with the mean score of students’ interest of using Note-Taking Strategy in learning listening is 84.47. Based on the result of this research, it can be concluded that the students are interested in learning listening through Note-Taking Strategy, in the other words, the students are in the high level of interest.